Learning and CRF-Induced Indecision during Escape and Submission in Rainbow Trout during Socially Aggressive Interactions in the Stress-Alternatives Model - Summers, Tangi R.; Summers, Torrie L.; Carpenter, Russ E.; Smith, Justin P.; Young, Samuel L.; Meyerink, Brandon; Orr, T. Zachary; Arendt, David H.; Summers, Cliff H. (Frontiers in Neuroscience, 2017)
Socially stressful environments induce a phenotypic dichotomy of coping measures for populations in response to a dominant aggressor and given a route of egress. This submission- (Stay) or escape-oriented (Escape) dichotomy represents individual decision-making under the stressful influence of hostile social environments. We utilized the Stress-Alternatives Model (SAM) to explore behavioral factors which might predict behavioral phenotype in rainbow trout. The SAM is a compartmentalized tank, with smaller and larger trout separated by an opaque divider until social interaction, and another divider occluding a safety zone, accessible by way of an escape route only large enough for the smaller fish. We hypothesized that distinctive behavioral responses during the first social interaction would indicate a predisposition for one of the behavioral phenotypes in the subsequent interactions. Surprisingly, increased amount or intensity of aggression received had no significant effect on promoting escape in test fish. In fact, during the first day of interaction, fish that turned toward their larger opponent during attack eventually learned to escape. Escaping fish also learn to monitor the patrolling behavior of aggressors, and eventually escape primarily when they are not being observed. Escape per se, was also predicted in trout exhibiting increased movements directed toward the escape route. By contrast, fish that consistently remained in the tank with the aggressor (Stay) showed significantly higher frequency of swimming in subordinate positions, at the top or the bottom of the water column, as well as sitting at the bottom. In addition, a corticotropin-releasing factor (CRF)-induced behavior, snap-shake, was also displayed in untreated fish during aggressive social interaction, and blocked by a CRF1 receptor antagonist. Especially prevalent among the Stay phenotype, snap-shake indicates indecision regarding escape-related behaviors. Snap-shake was also exhibited by fish of the Escape phenotype, showing a positive correlation with latency to escape. These results demonstrate adaptive responses to stress that reflect evolutionarily conserved stress neurocircuitry which may translate to psychological disorders and decision-making across vertebrate taxa.